Trinidad and Tobago. Significant achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Trinidad and Tobago during 2019 are identified, with respect to the needs and interests of the country, strengthening sustainable food production systems, exchange between public and private companies, the cocoa industry, cassava and citrus fruits and good agricultural practices, such as health and food safety (SAIA). Provided technical assistance for the development of risk management and response capacity, on issues such as floods. Finally, work was done on pest control, sustainability and profitability of agriculture, as well as promoting the development of agribusiness.